Estimate of Sediment Pickup Rate with the Densimetric Froude Number - Chen, Nian-Sheng (2016)
The present study shows that the sediment pickup rate is better correlated with the densimetric Froude number than the Shields number. With laboratory data collected in open channel flows, an empirical formula for estimating the pickup rate is proposed. Because it does not involve the critical condition for the incipient sediment motion, the formula can be applied to sediment entrainment of different stages including weak sediment motion. In spite of the fact that the experiments were carried with a limited range of sediment particle diameters, ranging from 0.23 to 0.86 mm, the results obtained are also supported by several series of data reported in the literature.